A retrospective evaluation of the steroid sparing effects of oral mycophenolate mofetil (MMF) as an adjunct immunosuppressant for the treatment of canine pemphigus foliaceus. Issue 1 (25th October 2021) - Putra, Andhika; Austel, Michaela; Banovic, Frane
Abstract : Background: Oral mycophenolate mofetil (MMF) currently is considered a low‐risk steroid‐sparing therapeutic option for the management of canine pemphigus foliaceus (PF). Objectives: This retrospective study evaluates the therapeutic outcomes of dogs with PF treated with the combination of oral MMF and glucocorticoid (GC). Clinical outcomes and adverse side effects are reported. Animals: Eleven dogs diagnosed with PF. Materials and methods: Retrospective review of medical records from dogs presented with PF to the dermatology service of a veterinary teaching hospital between 2015 and 2020. Results: Eleven dogs were identified which had received concurrent GCs and MMF. The MMF dose range was 19.8–45 mg/kg/day. Only two dogs (two of 11) treated with a mean MMF dosage of 39 mg/kg/day along with oral prednisone or dexamethasone achieved complete remission (CR). Partial remission (PR) was achieved in four of 11 dogs who received either prednisone, prednisolone or dexamethasone along with MMF (mean dosage 26 mg/kg/day). Four dogs (four of 11) showed poor response to MMF given at 28.5 mg/kg/day along with prednisone or dexamethasone. In one dog (one of 11) MMF was discontinued due to severe GI upset; transient vomiting and diarrhea was observed in four of 11 dogs. The median duration of MMF therapy in conjunction with GC for all groups was 70.5 days. Tapering of oral GCs while continuing MMF administration at the same dosage and frequency led to recurrence of lesions in all PF patients. Conclusion: Oral MMF combined with GC achieved CR in two of 11 PF dogs included in this study. Further research of MMF efficacy in PF may need to be performed. Abstract : Background – Oral mycophenolate mofetil (MMF) is currently considered a low‐risk steroid‐sparing therapeutic option the management of canine pemphigus foliaceus (PF). Objectives – This retrospective study evaluates the therapeutic outcomes of dogs with PF treated with the combination of oral MMF and GC. Clinical outcomes and side effects are reported. Conclusion – Oral MMF combined with GC achieved CR in 2 out of 11 PF dogs included in this study. Further research of MMF efficacy in PF may need to be performed. Résumé: Contexte: Le mycophénolate mofétil (MMF) oral est actuellement considéré comme une option thérapeutique d'épargne des corticoïdes à faible risque pour la prise en charge du pemphigus foliacé (PF) canin. Objectifs: Cette étude rétrospective évalue les résultats thérapeutiques des chiens atteints de PF traités par l'association de MMF et GC par voie orale. Les résultats cliniques et les effets secondaires sont rapportés. Animaux: Onze chiens diagnostiqués avec PF. Méthodes: Revue rétrospective des dossiers médicaux des chiens présentés avec PF au service de dermatologie d'un CHU 2015‐2020. Résultats: Onze chiens ayant reçu simultanément des GC et MMF ont été identifiés. Les doses de MMF variaient de 19, 8 à 45 mg/kg/jour. Seuls deux chiens (2/11) traités avec une dose moyenne de MMF de 39 mg/kg/jour avec de la prednisone ou de la déxaméthasone par voie orale ont obtenu une rémission complète (RC). Une rémission partielle (RP) a été obtenue chez 4/11 chiens qui ont reçu soit de la prednisone, de la prednisolone ou de la déxaméthasone avec du MMF (dose moyenne de 26 mg/kg/jour). Quatre chiens (4/11) ont montré une faible réponse au MMF administré à 28, 5 mg/kg/jour avec de la prednisone ou de la déxaméthasone. Chez un chien (1/11), le MMF a été interrompu en raison de troubles gastro‐intestinaux graves ; des vomissements et des diarrhées transitoires ont été observés chez 4/11 chiens. La durée médiane du traitement par MMF en conjonction avec le GC pour tous les groupes était de 70, 5 jours. La diminution des GC orales tout en continuant l'administration de MMF à la même dose et à la même fréquence a entraîné une récurrence des lésions chez tous les patients atteints de FP. Conclusion: Le MMF oral combiné aux GC a obtenu une RC chez 2 des 11 chiens PF inclus dans cette étude. D'autres recherches sur l'efficacité du MMF dans le PF peuvent être nécessaires. Resumen: Introducción: el micofenolato de mofetilo (MMF) oral se considera actualmente una opción terapéutica de bajo riesgo para disminuir esteroides en el tratamiento del pénfigo foliáceo (PF) canino. Objetivos: este estudio retrospectivo evalúa los resultados terapéuticos de los perros con PF tratados con la combinación de MMF oral y glucocorticoides (GC). Se reportan los resultados clínicos y los efectos secundarios. Animales: once perros diagnosticados con PF. Métodos: Revisión retrospectiva de historias clínicas de perros presentados con PF al servicio de dermatología de un hospital universitario veterinario 2015‐2020 Resultados: se identificaron once perros que habían recibido GC y MMF simultáneos. El rango de dosis de MMF fue de 19, 8 a 45 mg/kg/día. Solo dos perros (2/11) tratados con una dosis media de MMF de 39 mg/kg/ día junto con prednisona o dexametasona oral lograron la remisión completa (RC). Se logró la remisión parcial (RP) en 4/11 perros que recibieron prednisona, prednisolona o dexametasona junto con MMF (dosis media de 26 mg/kg/día). Cuatro perros (4/11) mostraron una mala respuesta al MMF administrado a 28, 5 mg/kg/día junto con prednisona o dexametasona. En un perro (1/11) se suspendió el MMF debido a un trastorno gastrointestinal severo; se observaron vómitos y diarrea transitorios en 4/11 perros. La duración media de la terapia con MMF junto con GC para todos los grupos fue de 70, 5 días. La disminución gradual de los GC orales mientras se continuaba con la administración de MMF a la misma dosis y frecuencia provocó la recurrencia de las lesiones en todos los pacientes con PF. Conclusión: el MMF oral combinado con GC logró RC en 2 de los 11 perros con PF incluidos en este estudio. Es posible que sea necesario realizar más investigaciones sobre la eficacia del MMF en el PF. Zusammenfassung: Hintergrund: Mycophenolat (MMF) per os wird momentan als Steroide‐sparende risikoarme therapeutische Option beim Management des caninen Pemphigus foliaceus (PF) betrachtet. Ziele: Diese retrospektive Studie evaluierte die therapeutischen Ergebnisse bei Hunden mit PF, die mit einer Kombination aus MMF per os und GC behandelt worden waren. Klinische Ergebnisse und Nebenwirkungen werden festgehalten. Tiere: Elf Hunde, die mit PF diagnostiziert worden waren. Methoden: Eine retrospektive Review der medizinischen Daten von Hunden, die dem Dermatologie Service einer veterinärmedizinischen Schulungsklinik zwischen 2015‐2020 mit PF vorgestellt worden waren. Ergebnisse: Es wurden elf Hunde gefunden, die gleichzeitig GCs und MMF erhalten hatten. Die MMF Dosis reichte von 19, 8‐45 mg/kg/Tag. Nur zwei Hunde (2/11), die mit einer durchschnittlichen MMF Dosis von 39 mg/kg/Tag und gleichzeitig mit Prednisolon oder Dexamethason behandelt worden waren, erreichten eine völlige Heilung (CR). Eine partielle Remission (PR) wurde bei 4/11 Hunden erzielt, die entweder Prednison, Prednisolon oder Dexamethason gleichzeitig mit MMF (durchschnittliche Dosis 26 mg/kg/Tag) erhielten. Vier Hunde (4/11) zeigten eine schlechte Reaktion auf MMF bei einer Dosis von 28, 5 mg/kg/Tag gleichzeitig mit Prednison oder Dexamethason. Bei einem Hund (1/11) wurde MMF aufgrund starker GI Nebenwirkungen abgesetzt; vorübergehendes Erbrechen und Durchfall wurde bei 4/11 Hunden festgestellt. Die mediane Dauer der MMF Therapie in Zusammenhang mit GC betrug für alle Gruppen 70, 5 Tage. Ein Ausschleichen der GCs per os während MMF bei gleicher Dosierung und Frequenz weiter verabreicht wurde, führte zu einem Wiederauftreten der Läsionen bei allen PF Patienten. Schlussfolgerung: MMF per os kombiniert mit GC erreichte eine CR bei 2 von 11 Hunden dieser Studie. Es sind weitere Studien in Bezug auf die MMF Wirksamkeit bei PF nötig. 要約: 背景: 経口ミコフェノール酸モフェチル (MMF) は、現在、犬の落葉状天疱瘡 (PF) の治療において、低リスクでステロイドを節約できる治療法と考えられている。 目的: 本回顧的研究は、経口MMF及びGCの併用療法を受けたPF犬の治療成績を評価するものである。臨床結果及び副作用が報告されている。 供試動物: PFと診断された11頭の犬。 方法: 獣医学教育病院の皮膚科サービスにPFで来院した犬の2015年から2020年の医療記録の回顧的レビュー 結果: GC及びMMFを同時投与された犬が11頭確認された。MMFの投与量は19.8˜45mg/kg/dayであった。平均MMF投与量39mg/kg/day及びプレドニゾンまたはデキサメタゾンの経口投与を受けた2頭 (2/11) のみが完全寛解 (CR) を達成した。MMFと同時にプレドニゾン、プレドニゾロン、デキサメタゾンを投与された4/11頭 (平均投与量26mg/kg/day) では、部分寛解 (PR) が得られた。4頭 (4/11) は、プレドニゾンまたはデキサメタゾンと同時に28.5mg/kg/dayのMMFを投与されたが、反応が悪かった。1頭の犬 (1/11) では、重度の胃腸障害のためにMMFの投与を中止した。4/11の犬では、一過性の嘔吐及び下痢が観察された。全グループにおけるGCと併用したMMF療法の期間の中央値は70.5日であった。MMFの投与を同量・同頻度で継続しながら、経口GCを漸減すると、PFの全症例で病変が再発した。 結論: MMFの経口投与及びGCの併用は、本研究に参加した11頭のPFのうち2頭でCRを達成した。PFにおけるMMFの有効性については、さらなる研究が必要であろう。 摘要: 背景: 口服吗替麦考酚酯(MMF)目前被认为是一种低风险的犬落叶型天疱疮(PF)治疗药, 可以减少类固醇的使用。 目的: 本回顾性研究评价了接受口服MMF和GC联合治疗犬PF的效果。报告临床疗效和副作用。 动物: 诊断为PF的11只犬。 方法: 回顾性审查2015‐2020年在兽医教学医院皮肤科就诊的PF犬病历。 结果: 确定了11只同时接受GC和MMF的犬。MMF剂量范围为19.8‐45 mg/kg/天。接受MMF平均剂量39 mg/kg/天, 联合经口给予泼尼松或地塞米松治疗, 仅两只犬(2/11)达到完全缓解(CR)。接受泼尼松、泼尼松龙或地塞米松联合MMF (平均剂量26 mg/kg/天) 的4/11只犬, 达到部分缓解(PR)。4只犬(4/11)对MMF 28.5 mg/kg/天联合泼尼松或地塞米松治疗反应不佳。在1只犬(1/11)中, 由于重度GI不适而停用MMF; 在4/11只犬中观察到一过性呕吐和腹泻。所有组MMF联合GC治疗的中位持续时间为70.5天。在以相同剂量和频率继续MMF给药的同时逐渐减少口服GC, 导致所有PF患犬病变复发。 结论: 本研究纳入的11只PF犬, 口服MMF联合GC, 2只达到CR。可能需要进一步研究MMF在PF中的疗效。 Resumo: Contexto: O micofenolato de mofetil por via oral (MMF) é atualmente considerado uma opção terapêutica de baixo risco capaz de reduzir a dose de esteroides no manejo do pênfigo foliáceo canino (PF). Objetivos: Este estudo retrospectivo avaliou a evolução terapêutica de cães com PF tratados com MMF e GC em associação. As respostas clínicas e os efeitos colaterais foram relatados. Métodos: Estudo retrospectivo dos prontuários de cães com PF atendidos no serviço de dermatologia de um hospital veterinário universitário de 2015‐2020. Animais: Onze cães diagnosticados com PF. Resultados: Onze cães que receberam a combinação de CGs e MMF foram identificados. A dose do MMF foi variou entre 19, 8‐45 mg/kg/dia. Apenas dois cães (2/11) tratados com uma dose média de MMF de 39 mg/kg/dia em associação com prednisona ou dexametasona por via oral alcançaram remissão completa (RC). A remissão parcial (RP) foi alcançada em 4/11 cães que receberam prednisona, prednisolona ou dexametasona em combinação com MMF (dosa média de 26 mg/kg/dia). Quatro cães (4/11) apresentaram resposta ruim ao MMF administrado na dose de 28, 5 mg/kg/dia junto com prednisona ou dexametasona. Em um cão (1/11), o MMF foi descontinuado devido a distúrbios gastrointestinais graves; vômitos transitórios e diarreia foram observados em 4/11 cães. A duração média da terapia com MMF em conjunto com GC para todos os grupos foi de 70, 5 dias. A redução gradual dos GCs orais com manutenção da administração de MMF na mesma dosagem e frequência levou à recorrência das lesões em todos os pacientes com PF. Conclusão: O MMF por via oral combinado com GC gerou RC em dois dos 11 cães com PF inclusos neste estudo. Mais estudos sobre a eficácia do MMF no PF são necessários.